2017
DOI: 10.1002/mnfr.201600528
|View full text |Cite
|
Sign up to set email alerts
|

A safflower oil based high‐fat/high‐sucrose diet modulates the gut microbiota and liver phospholipid profiles associated with early glucose intolerance in the absence of tissue inflammation

Abstract: We suggest that a diet-dependent increase in the n-6 to omega-3 (n-3) PUFA ratio in hepatic phospholipids together with gut microbiota changes contributed to early development of glucose intolerance without signs of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Blautia is a Gram‐positive, anaerobe bacterium belonging to the family Lachnospiraceae , which was thought to take part in the development of glucose metabolism disturbances . In addition, a safflower oil based high‐fat/high‐sucrose diet resulted in an increased abundance of Blautia . In the current study, Blautia was much higher in DM compared with NC, but in the gut of low, middle, and high dose perilla oil‐fed KKAy mice, Blautia was lower than DM.…”
Section: Discussionmentioning
confidence: 40%
“…Blautia is a Gram‐positive, anaerobe bacterium belonging to the family Lachnospiraceae , which was thought to take part in the development of glucose metabolism disturbances . In addition, a safflower oil based high‐fat/high‐sucrose diet resulted in an increased abundance of Blautia . In the current study, Blautia was much higher in DM compared with NC, but in the gut of low, middle, and high dose perilla oil‐fed KKAy mice, Blautia was lower than DM.…”
Section: Discussionmentioning
confidence: 40%
“…We also found that the relative abundance of Parasutterella in Adenine Group was significantly lower than that in Sham group, while α -ketoacid intervention tended to increase the abundance of Parasutterella . In a variety of animal models and human studies, a marked decrease of Parasutterella has been observed after high-fat diet (HFD) treatment, indicating a negative correlation was existed between the abundance of Parasutterella and HFD-induced metabolic abnormality ( Zhang et al, 2012 ; Danneskiold-Samsoe et al, 2017 ). As for Anaerovorax , it has been approved as butyrate producers ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Parasutterella (Proteobacteria) has been defined as a core component of the healthy human and mouse gut microbiota and has been correlated with various health outcomes (33), including inflammatory bowel disease (IBD) (34), obesity (35,36), diabetes (37), fatty liver disease (38), chronic kidney disease (39), major depression (40), Henoch-Schönlein purpura in children (41), cholestasis in infants (42), and Hashimoto's thyroiditis in patients (43). A reduction of Parasutterella in response to an HFD has been observed in both animal models and human studies, indicating a positive correlation between Parasutterella abundance and HFD-induced metabolic phenotypes (44)(45)(46). Our results also showed that the abundance of Parasutterella increased significantly after the induction of the HFD, but ALA reversed this change.…”
Section: Discussionmentioning
confidence: 99%